(3JQJjH GdKbGJ dGHf MHGfs - (3Ydj Hf CHj HcQ Hf SdjeGf GdgjKej, CHh GdMSf, fhQ GdOjf, GdeUQj GdbGgQj,J (B807 (3g` s
(3ChdgG (B:s
(3jHJOF HJQLeI GdCMeOjf s
(3BNQgG (B:s
(3jfJgi HJQLeI ef GSeg UHM HaJM GdUGO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B45s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B91 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eUWdM GdMOjK (B37) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdJGQjNs